Kemampuan Maturasi dan Fertilisasi Oosit Sapi yang Diseleksi Menggunakan Teknik Pewarnaan Brilliant Cresyl Blue (SELECTING MATURATION AND FERTILIZATION ABILITY OF BOVINE OOCYTES USING BRILLIANT CRESYL BLUE) - Muttaqin, Zultinur; Karja, Ni Wayan Kurniani; Setiadi, Mohamad Agus (Jurnal Veteriner; Vol 16 No 2 (2015), 2015)
The objective of this study was to evaluate the use of brilliantcresyl blue (BCB) in selecting potentialbovine oocytes for maturation and fertilization in vitro. Brilliant cresyl blue (BCB) is a dye that can assessintracellular activity of glucose-6-phosphate dehydrogenase (G6PD), a synthesized enzyme in maturedoocytes. Oocytes were exposed to 26 ?M BCB diluted in modified Phosphate Buffer Saline (mPBS, PBS +10% Fetal Bovine Serum) for 90 minutes is 5% CO2 incubator at 390C. The oocytes were classified accordingto their cytoplasm coloration: oocytes with blue cytoplasm (BCB+) and unstained oocytes (BCB-). Oocytesof the control group were incubated shortly after morphological selection without being exposed to BCB.Afterwards, all groups of oocytes (BCB+, BCB-, and control) were matured and fertilized in vitro. Maturedoocytes were those oocytes that reach metaphase II after 24 hours culturing; whereas oocytes showing twoor more pronuclei at 14 hours post incubation were classified as fertilized oocytes. The nuclear maturationrate was significantly (P<0.05) higher in BCB+ group (78.7% ± 0.41) than the BCB- group (33.3% ± 0.13).However, there was no significance difference (P>0.05) between the BCB+ and the control group (77.1% ±0.32). The fertilization rate was significantly higher (P<0.05) in the BCB+ group (30.5% ± 0.04) comparedto the BCB- (13.6%±0.03) and control group (23.6% ± 0.05). In conclusion, BCB staining of bovine oocytesprior in vitro maturation could be used in selecting potential developing oocytes.
Keywords: oocytes, brilliant cresyl blue, maturation, fertilization